ANALISIS PENGARUH KUALITAS PELAYANAN, NILAI PELANGGAN, DAN EXPERIENTIAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN ULANG MELALUI KEPUASAN PELANGGAN (Studi Pada Subasuka Paradise Restaurant di Kupang) - Theressa Lisye Purek, Maria; Khasanah, Imroatul (Diponegoro Journal of Management, 2018)
The purpose of this study is to analyze cause of sales decline in Subasuka Paradise Restaurant and find solutions to customer complaints. This study is to analyze the impact of service quality, customer value, and experiential marketing over repurchase decision through customer satisfaction in Subasuka Paradise Restaurant Kupang.The research was conducted to Subasuka Paradise Restaurant’s customers who did transaction with Subasuka Paradise Restaurant for more than twice. The total of sample used in this research is 120 respondents with questionnaire as the collecting data method and non probability sampling as sampling method used with purposive sampling technique. The research used Structucal Equation Modelling as analyze technique which is estimated with SEM AMOS 22.0 program.The result stated that customer value have the strongest and the most significant effect on customer satisfaction, followed by expreriential marketing, while servi didn’t have a direct and indirect impact over repurchase decision through customer satisfaction. While service quality has the weakest effect and doesn’t significantly affect the customer satisfaction to affect repurchase decision. Customer satisfaction factor is the main factor which is able to influence the buyer to do repurchase, so that the higher one customer’s satisfaction rate the higher the decision to do repurchase to the product and service